GENDER AND SEXUALITY: EXPERIENCES AND CONCEPTS OF YOUNG UNIVERSITY STUDENTS FROM THE PSYCHOLOGY COURSE IN THE CITY OF SAO PAULO - Tedeschi Cano, Marina [UNESP]; Leivar Brancaleoni, Ana Paula [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2022)
It has been necessary to broaden the debate and struggles against both sexual and gender inequalities. This article aims to identify the understandings of young university students, enrolled of Psychology courses at private higher education institutions in the city of Sao Paulo, about sexuality and gender, as well as your formative role in relation to the subject. The qualitative approach was adopted and interviews with ten university students were conducted by Thematic Analysis and it was found that: institutions do not deal with gender and sexuality-related issues; there is little or no space for debate and discussion on the topic; institutions have not been a vehicle for obtaining information about the subjects; prejudice and discrimination are reproduced in institutional practices; university students' relationships among their peers participate in the construction of their conceptions about sexuality. The found data highlight the importance of creating / expanding spaces for reflection and discussion related to gender and sexuality in Higher Education.
Keywords: Gender; Sexuality; College students; Sex education